Catholic human rights movement in Lithuania: the most active period (1972–1982) - Streikus, Arūnas (Genocidas ir rezistencija, 2003)
The Catholic Church’s struggle for the rights of the faithful has been uninterrupted since the onset of the Soviet occupation. In the first decades, the Church hierarchs were the initiators of the resistance against the restrictions on religious life. By the early 1960s, however, the Soviet authorities had succeeded in neutralising the resistance from above, and from then onwards they were quite effectively controlling the moods and actions of diocesan governors. Therefore, a few years later, the initiative to stop the further deterioration of the situation of the Church was already taken by ordinary priests and the congregation. We will try to discuss, in more detail, the second stage, which is characterised by the greatest activism of the congregation, as well as to highlight its specificities and its impact on the policy of the Soviet authorities.
Keywords: civil resistance; religious resistance; KGB; Soviet religious policy; Catholic Church